TINGKAT KEPUASAN KONSUMEN PADA CAFE GUDANG IMAJI COFFEE KECAMATAN WENANG KOTA MANADO (Level of Customer Satisfaction in the Gudang Imaji Cafe, Wenang District City of Manado) - Theovani Dwyanti Lian; G. H. M. Kapantow; Ribka M. Kumaat (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
This study aims to measure the level of consumer satisfaction at Cafe Gudang Imaji, in terms of product, price, place, promotion, and service aspects. This research was conducted from March to June 2020. Primary and secondary data were used in this study. Respondents consisted of 30 people were selected using accidental sampling technique. Data were measured in the Likert scale, and then analyzed using the Consumer Satisfaction Index (CSI).In general, the level of consumer satisfaction at the Cafe Gudang Imaji was classified as satisfied with CSI = 83.80%. More specifically for each apect, the satisfaction level for product (85.11%), prices (87.33%) and services (86.67%) were classified as very satisfied, while place (79.60%) and promotion (78.00%) only belonged to satisfied category.Keywords: Level of Satisfaction, Consumer Satisfaction Index, Gudang Imaji Cafe